Tales from Thailand - Toth, Marian Davies; Supes Pasutanavin (Rutland, Vt. Tuttle, 1971)
A retelling of eighteen traditional Thai folk tales, followed by a brief section on the history, geography, culture, and people of the "Land of Smiles."
Keywords: Tales -- Thailand; Folklore -- Thailand